2018
DOI: 10.1007/978-981-10-8456-0_5
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Function of Influenza Virus Ribonucleoprotein

Abstract: Influenza is a negative-sense single-stranded RNA virus with segmented genome. Each segment is encapsidated by a ribonucleoprotein (RNP) complex composed of RNA-dependent RNA polymerase (RdRP) and multiple copies of nucleoprotein (NP). The RNP complex plays a crucial role in viral life cycle, supporting and regulating transcription and replication of viral genome in infected cells. The structural characterization of RdRP and RNP in recent years has shed light on its functions and mechanism of action. In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 99 publications
0
31
0
Order By: Relevance
“…For investigating the driving force that increases the odds of any identified low-frequency variant to emerge at the consensus level, we tested three parameters: variant genomic position, its prevalence among patients, and its prevalence across years using Fisher s exact tests for categorical variables embedded in Prism7 [47]. p-values < 0.01 were considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…For investigating the driving force that increases the odds of any identified low-frequency variant to emerge at the consensus level, we tested three parameters: variant genomic position, its prevalence among patients, and its prevalence across years using Fisher s exact tests for categorical variables embedded in Prism7 [47]. p-values < 0.01 were considered statistically significant.…”
Section: Discussionmentioning
confidence: 99%
“…The influenza virus RNA polymerase is composed of the proteins polymerase basic 1 (PB1), PB2, and polymerase acidic (PA) (P3 in influenza C and D viruses) ( Fig. 2A; te Pflug et al 2017;Lo et al 2018). X-ray crystallography and cryo-EM studies showed that the RNA polymerase consists of a core domain and several peripheral domains that are connected to the core through highly flexible linkers (Pflug et al 2014;Reich et al 2014;Chang et al 2015;Hengrung et al 2015;Thierry et al 2016;Fan et al 2019;Peng et al 2019).…”
Section: Architecture Of the Rna Polymerasementioning
confidence: 99%
“…provided novel insights into the mechanisms by which influenza viruses transcribe and replicate their RNA genome (te Pflug et al 2017;Lo et al 2018). These studies have answered fundamental questions about influenza RNA polymerase function and contributed to our understanding of the dependence of the influenza virus on host factors for the transcription and replication of its genome.…”
mentioning
confidence: 99%
“…Influenza viruses contain an eight segmented negative-sense, single-stranded viral RNA genome that encodes for at least eleven essential viral proteins. Each RNA segment is encapsulated into a ribonucleoprotein (RNP) molecule, consisting of the nucleoprotein (NP) and a trimeric RNA-dependent RNA polymerase (RdRp) complex composed by PA, PB1, and PB2 [ 6 ]. Inside the nucleus, the RdRp carries out transcription and replication using the vRNA as a template for both transcription to mRNA and synthesis of complementary RNA (cRNA) that serves as the template for novel vRNAs.…”
Section: Introductionmentioning
confidence: 99%